2013
DOI: 10.3166/rfg.233.15-32
|View full text |Cite
|
Sign up to set email alerts
|

Les administratrices des grands groupes français cotés Quels « atouts » privilégier ?

Abstract: Les administratrices des grands groupes français cotésQuels « atouts » privilégier ? La loi n° 2011-103 du 27 janvier 2011 fixe au seuil de 40 % la proportion de femmes devant siéger dans les conseils d'administration des entreprises françaises cotées. Par conséquent, entre 550 et 1 350 postes d'administratrices seront à pourvoir à l'horizon 2017. Cet article examine la nature de la légitimité des femmes -c'est-à-dire leurs « atouts » -à siéger dans les conseils d'administration afin d'esquisser un profil des … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 12 publications
(23 reference statements)
1
4
0
2
Order By: Relevance
“…This is another French specificity which accounts for traditionally strong links between large firms' boards and the French Government (Bourdieu, 1996;Moulin & Point, 2012a). Many graduates from these Elite schools, which train high-flying civil servants, had and still have albeit to a lesser extent privileged access to top positions in large French firms.…”
Section: Grands Corpsmentioning
confidence: 99%
“…This is another French specificity which accounts for traditionally strong links between large firms' boards and the French Government (Bourdieu, 1996;Moulin & Point, 2012a). Many graduates from these Elite schools, which train high-flying civil servants, had and still have albeit to a lesser extent privileged access to top positions in large French firms.…”
Section: Grands Corpsmentioning
confidence: 99%
“…Cette procédure permet, dans un premier temps, une sélection automatique du nombre de classes, grâce à des critères d'information permettant de comparer différents modèles (BIC : critère d'information bayésien, ou AIC : critère d'information d'Akaike). Ensuite, elle permet de faire émerger les variables qui ont fortement (ou faiblement) contribué à structurer le classement, de comparer les différentes classes sur des variables internes et externes à la classification (Moulin et Point, 2013).…”
Section: Méthodes De Traitement Des Donnéesunclassified
“…In another development, literature has also provided non-existence of relationship between gender diversity and performance in both developed countries and developing countries (Carter, D'Souza, Simkins, & Simpson, 2010;Zemzem & Kacem, 2014;Alm & Winber, 2016;Garanina & Kaikova, 2016;Sila et al, 2016). Again, it was equally shown that research on women directorship in relation to corporate value creation in developing country like Iraq is not specifically addressed by the literature, as most previous studies only focused on the -122 -© 2018 Prague Development Center association between family ownership and the number of female directors (Moulin & Point, 2012;Nekhili & Gatfaoui, 2013).…”
Section: Relationship Between Women Board Representation and Firm Permentioning
confidence: 99%